Artificially engineered vesicular vehicles for targeted therapy - Zhigang Wang; Yufei Yan; Rui Li; Ying Zhu; Gen Yang (Extracellular Vesicle)
Vesicular vehicles have been one of the most potential platforms for therapeutic delivery. Here, we commentate on recent advances in the development of therapeutic vesicular delivery platforms, emphasizing two intriguing works, namely, the chimeric nanobody-decorated immunoliposomes (Wan et al.) and the retrovirus-like capsids incorporated extracellular vesicles (Jiang et al.). In the work of Wan et al., the researchers proposed a novel strategy for antitumor immunoliposome construction by the one-step self-assembly of lipids with rationally designed chimeric nanobody that comprises a nanobody against human epidermal growth factor receptor 2, a flexible peptide linker, and a human single transmembrane domain. By leveraging the natural cell systems (e.g., E coli.) to synthesize the chimeric nanobody, this technique provides a facile and robust strategy for producing immunoliposome platforms, ensuring suitability for industrial manufacturing and distribution, regulatory compliance, and clinical use. In the work of Jiang et al., taking advantage of the natural extracellular vesicle biogenesis system, the researchers introduced the activity-regulated cytoskeleton-associated protein inside the vesicle lumen and thus constructed endogenous retrovirus-like vesicles for mRNA drug delivery to neurons. This technique offers a significative strategy for developing sophisticated delivery platforms, manifesting broad application potential for different disease therapeutics. Overall, these two works have represented two typical paradigms for the artificial construction of vesicular vesicles. Considering their complementary merits, in the future, the integration of artificial engineering technologies and natural biosynthesis systems is anticipated to be a promising strategy to expedite the development of potent delivery systems.